The Relationship between Temperament and Dental Anxiety in Children Aged 6 to 11 Referred to Yazd Dental School - Zahra Bahrololoomi; Fatemeh Zarebidoki; Amene Hosseini-Yekani; Parisa Boostanifard (Mashhad University of Medical Sciences, 2023)
Introduction: Dental anxiety is one of the complications of dental treatments in children and it is affected by many factors such as gender, age, and temperament. Therefore, the present study aimed to determine the relationship between children's temperament and dental anxiety in children aged 6 to 11 years referred to Yazd Dental School.Materials and Methods: This is a descriptive-analytical cross-sectional study in which 152 children aged 6 to 11 years were studied who referred to the pediatric dentistry department of the Faculty of Dentistry, Shahid Sadoughi University of Yazd, Iran in 2021. The data were collected using EAS (Emotion, Activity, sociability) temperament questionnaire and also MCDAS (Modified Child Dental Anxiety Scale) anxiety questionnaire. Finally, the relationship between the score of temperament dimensions and that of pediatric dental anxiety was analyzed by the Pearson correlation coefficient test using SPSS software. The significance level was considered at 0.05.Results: A significant correlation was observed between dental anxiety score and emotional score (P-value=0. 012, r=0. 203). This relationship was also significant and positive between dental anxiety and shyness score (P-value=0. 004, r=0. 232). Dental anxiety and dimensions like physical activity and sociability were negatively and significantly related (P-value=0. 031, r=-0. 175 and P-value=0. 048, r=-0. 161, respectively. A regression model was used to estimate the anxiety score using the scores of different mood dimensions. The result is R2=0. 1 which means 10% of the changes in the dependent variable is explained by the regression model. In this model, only the temperament dimension of emotion is effective in the anxiety score.Conclusion: According to the results of this study, decreasing the score in emotional and shyness dimensions and increasing the score in physical activity and sociability can reduce the dental anxiety of children during dental treatment. The regression model confirmed the effect of the emotional dimensions in increasing the anxiety score which can be achieved by psychologists and creating appropriate conditions and behaviors.